Razor blade ingestion in an infant: A case report (Journal of Paediatric Surgeons of Bangladesh, 2023)
Background: Foreign body (FB) ingestion is common in children and most are observed to be between the age of 6 months and 3 years. Usually, majority of cases require no specific treatment and the swallowed foreign body passes through the digestive tract spontaneously without causing significant complications. Less than 1% of the cases complicate by gastrointestinal tract perforation, which is often caused by sharp objects, and warrants surgical intervention. The majority of razor blade ingestions involve prisoners and psychiatric patients, but in paediatric patients it is rare and no cases are reported yet. Our patient is a 9-month-old girl who ingested a razor blade while playing. On radiological investigation, a razor blade like foreign body was found in the stomach. After emergency laparotomy, a single 2.5×1 cm razor blade was detected and carefully and safely removed. The patient was subsequently discharged home on the 5th POD with recommended family diet.Journal of Paediatric Surgeons of Bangladesh (2018) Vol. 9 (1&2): 53-56